PENGARUH LAJU PERTUMBUHAN PENDUDUK BERDAMPAK PADA TINGGINYA ANGKA KEMISKINAN YANG MENYEBABKAN BANYAK EKSPLOITASI ANAK DI INDONESIA - Nadia Cavina Putri; Nunung Nurwati (Jurnal Ilmu Kesejahteraan Sosial HUMANITAS, 2021)
The rapid population growth indicates an indication of poverty and increasing crime that is increasingly widespread, one of which is the increasing exploitation of children, especially in Indonesia. Because from year to year the rate of population growth has increased the graph of child exploitation significantly. This happens because the high rate of population growth cannot keep up with the level of the economy, because more and more needs must be fulfilled along with high population growth which causes many parents who have low economies to exploit children. Exploitation of children negatively impacts the children themselves, both of which have an impact on children's education, health, and psychology. Seeing this the government must be even more assertive in dealing with cases of child exploitation.